Ammonia volatilization from flooded rice soil using CAS and OSC methods - S., VANITHA; RAVIKUMAR, V.; RAJAMMAL, T. SHERENE JENITA (Journal of Soil and Water Conservation, 2021)
Ammonia (NH3-N) volatilization is an important process of nitrogen loss from crop production systems. An essential step in mathematical modeling is the determination of rate constants of urea reactions in soils. Accordingly, an experiment was conducted and reaction rate constant was estimated using two methods of ammonia recovery from urea applied to flooded rice field. Open Static Chamber (OSC) method is very simple and easy to implement in the field whereas Compressed Air Supply (CAS) method is costly and normally used in laboratory conditions. We adapted the CAS method for implementing in the field. The ammonia recovery from both the methods is approximately same and the observed ammonia volatilization was used for estimating reaction rate constants. The estimation of ammonia recovery and reaction rate constants did not vary significantly between the methods, viz. OSC and CAS. The partial differential equations representing nitrogen reaction process were solved using risk solver platform in the MS-EXCEL environment.